Critical Synthesis Package: Jefferson Scale of Patient Perceptions of Physician Empathy (JSPPPE) - Lindsey Dorflinger; Kristina Schumann (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education of the Jefferson Scale of Patient Perceptions of Physician Empathy (JSPPPE), and (2) a copy of the JSPPPE and supplementary files (i.e., reference materials) developed by Mohammadreza Hojat, PhD. The JSPPPE is a 5-item instrument; response options are presented along a 7-point Likert-type scale with 1 being "strongly disagree" and 7 being "strongly agree." The measure is completed by patients, and is used to assess physician empathy from the patient's perspective. Scores on the JSPPPE have been shown to correlate with provider self-ratings of empathy using the Jefferson Scale of Empathy, as well as other measures and items that tap physician empathy. The measure is brief, easy to use, and appears to demonstrate adequate internal consistency reliability and concurrent validity. Little information is provided by developers regarding the development of the scale, including how specific items and the number of scale items were chosen, and the studies utilizing the measure have used a somewhat restricted sample of physicians (i.e., providers working at the institution at which the instrument was developed). Future studies should examine the psychometric properties and utility of the measure in additional samples.